Pengaruh Brand Image, Brand Awarreness, Dan Brand Trust Terhadap Brand Loyalty Pada Batik Tulis Dewi Rengganis - Haidiputri, Trivosa Aprilia Novadiani; Rustianawati, Mutimmah; Lidyana, Novita; Safitry, Salwa Nadea (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2025)
This research aims to determine the influence of Brand Image, Brand Awareness, and Brand Trust on Brand Loyalty in Dewi Rengganis Written Batik, Probolinggo Regency simultaneously, partially and which variable is dominant. The type of research used was quantitative descriptive, with a sample size of 35 respondents. Determination of samples using simple random sampling techniques. The data analysis methods used include validity and reliability tests, classical assumption tests, R2 determination analysis, multiple linear regression tests and f tests (simultaneous) and t tests (partial). The test results show that simultaneously, Brand Image, Brand Awareness, and Brand Trust influence Brand Loyalty. Partially, it shows that Brand Image, Brand Awareness, and Brand Trust influence Brand Loyalty. Meanwhile, the variable that has the dominant influence on Brand Loyalty is the Brand Image variable